2012
DOI: 10.1007/s10047-011-0619-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair for abdominal aortic aneurysm concomitant with iliac arterial disease using InterGard™ Quadrifurcated

Abstract: InterGard™ Quadrifurcated [InterVascular S.A. (MAQUET Cardiovascular), La Ciotat, France], a knitted quadrifurcated prosthetic graft, is useful to simplify the procedures for patients with abdominal aortic aneurysm concomitant with iliac arterial disease. From March 2008 to April 2010, 59 patients underwent abdominal aortic aneurysm repair in our department. InterGard™ Quadrifurcated was used in 22 patients (37.3%). All patients were male with a mean age of 72.1 ± 12.1 years (range from 45 to 90 years). Four w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…IIAs are also a common complication after endovascular aortic repair (3). Some studies (4)(5)(6) have reported an association between IIAs and aortic aneurysms, showing an IIA incidence of 10-20% (7) in patients with aortic aneurysms.…”
mentioning
confidence: 99%
“…IIAs are also a common complication after endovascular aortic repair (3). Some studies (4)(5)(6) have reported an association between IIAs and aortic aneurysms, showing an IIA incidence of 10-20% (7) in patients with aortic aneurysms.…”
mentioning
confidence: 99%